ANALISIS MANAJEMEN STRATEGI DALAM MENGHADAPI PERSAINGAN BISNIS PT TIRTA INVESTAMA DC CIBINONG KABUPATEN BOGOR - Fauzan Al Bukhori; Ahmad Nurhadi (Journal of Research and Publication Innovation, 2025)
This research aims to analyze the strategic management practices implemented by PT Tirta Investama D.C. Cibinong in addressing business competition within the bottled water industry (AMDK). The background of this study pertains to the intensifying competition in the Indonesian AMDK market, where PT Tirta Investama, as the leading company, is confronted with challenges from emerging competitors and evolving consumer preferences. The study employs a qualitative research method with a case study approach, incorporating interviews with managerial personnel and secondary data derived from the company’s business profile and other pertinent sources. The findings indicate that PT Tirta InvestamaD.C. Cibinong has adopted several strategies to maintain its market leadership, including product innovation, brand reinforcement, and the optimization of product distribution. Additionally, the company engages in regular evaluations through consumer satisfaction surveys. Based on the results, it can be concluded that PT Tirta Investama's strategic management approach is effective in sustaining its market share and strengthening its competitive position in the Indonesian AMDK market.